Videocapillaroscopic Findings in Patients With Systemic Lupus Erythematosus With or Without Jaccoud Arthropathy. (September 2021) - Pimenta da Fonseca, Emanuela; Lins, Carolina Freitas; de Sá Ribeiro, Daniel Lima; Santos, Willer Gonçalves Dourado; Rosa, Genevievi; Machicado, Viviane; Pedreira, Ana Luiza; Souza, Anna Paula Mota Duque; Baleeiro, Carla; dos Santos Ferreira, Luana Grazielle; de Oliveira, Isabela Silva; da Silva, João Paulo Cotrim Gama; et al.
Abstract : Background/Objective: Systemic lupus erythematosus (SLE) is an autoimmune disease that can present changes in blood vessels, which can be evaluated by periungual nailfold videocapillaroscopy (VCP). This technique is important for the diagnosis of systemic sclerosis and to identify individuals with Raynaud phenomenon at higher risk of developing systemic sclerosis. This study aims to describe the videocapillaroscopic profile of a series of SLE patients and to investigate if the VCP pattern is different among those with Jaccoud arthropathy (JA) compared with those without. Methods: Between September 2014 and March 2015, the patients in this study underwent VCP, clinical evaluation, and laboratory tests. The capillaroscopic patterns were defined as minor, major, and scleroderma (SD). The presence of capillaroscopic findings, such as elongated capillaries, tortuosity, ectasia, prominent venous plexus, neoangiogenesis, hemorrhage, and megacapillaries, were also observed. Associations were calculated using the χ 2, Fisher exact, or Student t test. Results: In a population of 113 females with SLE (67 without JA and 46 with JA), at least 1 alteration was observed in VCP in 89.40% of them, among which "nonspecific changes" were the most prevalent. Minor changes were seen in 39 (58.2%) and 26 (56.5%), major changes in 21 (31.3%) and 11 (23.9%), and SD pattern in 2 (3.0%) and 3 (6.5%), in the patients without and with JA, respectively ( p > 0.05). Conclusions: The majority of patients with SLE demonstrated changes in the VCP examination, but this tool did not allow discrimination between those with or without JA.